Acetylsalicylic Acid - Schrör, Karsten (De Gruyter, 2022)
Written by a leading expert on Aspirin-related research, this is the most comprehensive treaty of the history, pharmacological effects and clinical applications of one of the most successful drugs ever. The text is written with a wide audience in mind and to be readily understandable for clinicians, pharmacists, biomedical researchers and pharmacologists alike. This third completely revised edition contains the latest results of clinical and pharmacological research on Acetylsalicylic acid, addressing the multiple pharmacological properties of this famous drug with a balanced view on their translation into clinical practice, including prevention and treatment of cardiovascular diseases, thromboinflammation and colorectal cancer.